Exploration on the Interaction Ability of Antitumor Compound Bis-[2,6-difluoro-N-(hydroxyl-<κ>O)benzamidato-<κ>O]dibutylitin(IV) with Human Peroxisome Proliferator-Activated Receptor hPPARγ - Jiaqi Mai; Yunlan Li; Xiaozhi Qiao; Xiaoqing Ji; Qingshan Li (Bioinorganic Chemistry and Applications)
Diorganotin(IV) antitumor compound bis-[2,6-difluoro-N-(hydroxyl-<κ>O)benzamidato-<κ>O] (DBDF2,6T) was one of the novel patent organotin compounds with high antitumor activity and relatively low toxicity. In this study, several methods were used to study the interaction between DBDF2,6T and hPPARγ protein, including fluorescence quenching, three-dimensional (3D) fluorescence, drug affinity responsive target stability (DARTS), ultrafiltration-LC, and molecular docking. According to the experimental results, the quenching process of the hPPARγ protein was induced by static quenching mode to form a nonradiative ground-state complex with DBDF2,6T spontaneously, mainly through the hydrophobic force. DBDF2,6T could bind to the hPPARγ protein directly and give the protein the ability of antienzymatic hydrolysis. And the binding mode of DBDF2,6T into hPPARγ protein appeared to have an orientation towards residues of SER342 and GLY284. In conclusion, these methods could comprehensively reveal the interaction details of DBDF2,6T and the hPPARγ protein and established a feasible way to preliminarily identify the agonist compounds for the hPPARγ protein.